'Holistic Sustainability' Policies: Preserving Local Cultural Identity in the UAE in the Face of Globalisation. (September 2019) - Daleure, Georgia
Fifty elders of the United Arab Emirates (UAE), recalling life before nationalisation in 1971, were interviewed to gain insight into their attitudes and beliefs as part of an investigation into how those beliefs are reflected in modern priorities of the UAE. The UAE was considered one of the poorest countries in the mid-1900s. Yet, after independence, utilising revenues from newly found oil reserves, a modernisation plan catalysed rapid development. For the UAE, holistic sustainability, encompassing cultural, economic, social and environmental dimensions, became the model for continued economic and political stability in a troubled region. The findings of the study revealed that the elders valued family closeness and education, depending on the contributions of women in society. These concepts carried forward into modern policies and legislation and emphasised by the leadership of the UAE to maintain cultural uniqueness yet thrive in the global social and economic environment.